Assessment of soil fertility status in cotton-based cropping systems in Cote d’Ivoire - Koné, Ismail; Kouadio, Konan-Kan Hippolyte; Kouadio, Emmanuel N’Goran; Agyare, Wilson Agyei; Owusu-Prempeh, Nat; Amponsah, William; Gaiser, Thomas (Frontiers in Soil Science, 2022)
Cotton is the main cash crop in northern Côte d'Ivoire. Continued use of cultivated areas with low external inputs has led to a decline in crop yields due to soil degradation. The present study aims to assess changes in soil fertility from 2013 to 2021 in the cotton basin area of Côte d'Ivoire. More precisely, the study (i) identified the limiting physico-chemical parameters of soil fertility, and (ii) analysed the state of evolution of soil fertility from 2013 to 2021 in the cotton basin of Côte d'Ivoire. For this purpose, a total of 64 soil samples were taken in 2013 and in 2021 on the same cotton plots in the 0-20 cm horizon. Chemical analyses of the soil samples in the laboratory were carried out on the following parameters: particle size distribution, pH water, total N, K+, Ca2+, Mg2+, Na+ and CEC. The results of the soil analyses showed that the sandy-clay textured topsoils dominate the whole study area in both years. This leads to a low retention capacity of exchangeable bases. Determination of the soil pH showed that the pH varies from slightly acidic to neutral (6.5